Supermassive black hole mergers as dual sources for electromagnetic flares in the jet emission and gravitational waves. Issue 9 (November 2013) - Tápai, M.; Gergely, L. Á.; Keresztes, Z.; Wiita, P.J.; Gopal‐Krishna; Biermann, P.L.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract We present a new type of observation relating the gravitational wave emission of supermassive black hole mergers to their electromagnetic counterparts. This dual emission involves variability of a relativistic jet arising from the spin‐orbit precession of the supermassive black hole binary at its base. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)